مبحث الإنسان في علم الكلام الجديد وحوار المذاهب والأديان - بوعيشة, أسمهان (جامعة الوادي - University of Eloued, 2022)
ملخص: أدت التطورات الفلسفية والاجتماعية الحديثة إلى الإعلاء من قيمة الإنسان في الكون وحقوقه ،وحريته ،وعلاقته ببعضه البعض .ومن هنا تبرز أسباب اختيار الموضوع كونه يعالج مدى حاجة الإنسان إلى الخوض في علاقته بالأخر عبر الإعلاء من القيم الإنسانية المشتركة ،وإظهار أن من مهام الدين في حياة الإنسان تكريمه ،وليس توظيف الدين لإثارة النعرات الطائفية والمذهبية والدينية ،وإذ ذاك كان علم الكلام الجديد في مُسحته الإنسانية الأكثر قدرة على إبراز المشترك الإنساني ووضع لبِنات للحوار المذهبي والديني .وتهدف هذه الورقة البحثية إلى التطرق إلى موضوع استرجاع الإنسان وتغليب نزعته الإنسانية في علاقته بالدين بعد أن غيَّبته الجدليات الكلامية الكلاسيكية ،والاهتمام بمتطلباته اليومية والعملية وتحقيق مصالحه وبُعده الإنساني في علاقاته مع المختلف مذهبيا ودينيا .ومن أهم نتائج هذا البحث أن من مهام علم الكلام الجديد في مستواه الإنساني التدليل على كونية وإنسانية الخطاب الكلامي الإسلامي وروحانيته عبر ترسيخ ثقافة التعايش والتسامح مع الأخر وقبول مبدأ الحوار بين المذاهب والأديان . Abstract : Modern philosophical and social developments have elevated the value of man in the universe, his rights, his freedom and his relations with other’s.Therefore, the reasons for the choice of the theme emerge, because it addresses the extent to which man needs to deepen his relationship with the other by raising common human values, and by showing that one of the tasks of religion in a person's life is to honor him, and not to use religion to stir up sectarian and religious conflicts, The new theology appears with its humanist tinge, capable of highlighting the human commonality and of laying the foundations for sect and religious dialogue .The aim of this research thesis is the question of human restoration and to give priority to its human tendency in its relation to religion, after it has been absent in the classical dialectic. One of the most important results of this research is that one of the tasks of the new theology at its human level is to show the universality and humanity of Islam and its spirituality through the consolidation of a culture of coexistence and tolerance with others and dialogue between sects and religions.
The Subject Of Man In The New Theology And The Dialogue Of Sects And Religion
مقال
Keywords: الإنسان؛ علم الكلام الجديد؛ الحوار المذهبي ؛ الحوار الديني .; Human; New Theology; Religious Dialogue ;Dialogue Between Sect